2020
DOI: 10.3389/fspor.2020.579830
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the German Strategy for Containment of Coronavirus SARS-CoV-2 on Training Characteristics, Physical Activity and Sleep of Highly Trained Kayakers and Canoeists: A Retrospective Observational Study

Abstract: Aim: To characterize the impact of the German strategy for containment of Coronavirus SARS-CoV-2 (social distancing and lockdown) on the training, other habitual physical activity, and sleep in highly trained kayakers and canoeists. Method: During the 4 weeks immediately prior to and following the beginning of the German government's strategy for containment of Coronavirus SARS-CoV-2 on March 23, 2020, 14 highly trained athletes (VO 2peak : 3,162 ± 774 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
0
33
0
1
Order By: Relevance
“…Similarly, Zinner et al ( 2020 ) observed reductions in overall weekly training time (−27.6%) and the average length of training sessions (−15.4%) during a COVID-19 lockdown period in highly trained German kayakers and canoeists. The authors also observed an increase in the number of strength-focused training sessions with no change in sport-specific activities, which is contradictory to the findings from the current study (Zinner et al, 2020 ). It is possible that athletes at the elite level may have had better access to strength equipment, thereby allowing for increased opportunities for strength workouts.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, Zinner et al ( 2020 ) observed reductions in overall weekly training time (−27.6%) and the average length of training sessions (−15.4%) during a COVID-19 lockdown period in highly trained German kayakers and canoeists. The authors also observed an increase in the number of strength-focused training sessions with no change in sport-specific activities, which is contradictory to the findings from the current study (Zinner et al, 2020 ). It is possible that athletes at the elite level may have had better access to strength equipment, thereby allowing for increased opportunities for strength workouts.…”
Section: Discussionmentioning
confidence: 79%
“…The authors noted 34% reductions in total training volume and reductions in weekly volumes across intensity zones ranging from 25 to 52% (effect size: 0.83-1.57) during the lockdown period, which contributed to reductions in maximal effort cycling performance (Muriel et al, 2020). Similarly, Zinner et al (2020) observed reductions in overall weekly training time (−27.6%) and the average length of training sessions (−15.4%) during a COVID-19 lockdown period in highly trained German kayakers and canoeists. The authors also observed an increase in the number of strength-focused training sessions with no change in sport-specific activities, which is contradictory to the findings from the current study (Zinner et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Google Trend analysis of community interest in physical activity during the COVID-19 outbreak and lockdown showed an increase in Google search rates on physical activity topics in Australia, the United Kingdom, and the United States [ 21 ]. A study among German athletes using activity tracker data showed that shorter and more vigorous exercise sessions replaced longer sessions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sonza et al [ 18 ] indicated that the COVID-19 pandemic influenced training practice and habits in term of frequency, duration, motivation, and period to exercise in Brazil and its main macro-regions. Furthermore, following the German lockdown for containment of the COVID-19 pandemic, highly trained kayakers and canoeists spent less overall time training each week (−28%) with, on average, shorter training sessions (−15%) and less light-to-moderate physical activity outside of training [ 19 ]. Additionally, de Albuquerque Freire et al [ 20 ] demonstrated that COVID-19-related restrictions and quarantine had adverse effects on professional soccer players’ Yo-Yo Intermittent Recovery Test performance.…”
Section: Introductionmentioning
confidence: 99%